Risk factors for ovarian postpartum resumption in Holstein cows, under high tropical conditions - Humberto Guáqueta M (Revista MVZ Córdoba, 2014)
Objective. To evaluate the factors associated with postpartum ovarian resumption and follicular dynamics in Holstein cows under high altitude conditions (2,600 masl). Materials and methods. Forty-five Holstein cows were studied between 14 days before and 120 days after calving. Uterine involution, follicular dynamics, serum progesterone and peripartum pathologies were evaluated; additionally, body condition (BC), calving type, milk yield, were also evaluated. According to hormonal and reproductive findings, cows were classified into two groups: early ovarian resumption (EOR) or delayed ovarian resumption (DOR). Results. The occurrence of the first follicular for EOR animals (n=31) was produced on average 9.58±3.45 days postpartum and was similar to the DOR group (n=10) [10.8±4.83 days; p>0.05)]. The first postpartum ovulation occurred at 21.55±5.90 days (EOR) and was significantly delayed (48.7±27.85 days) for DOR animals (p<0.05). Thirty-six point five percent of the cows (n=f) had normal estrus cycles (18 to 24 days), while 63.5% (n=26) showed dysciclia. The factors associated with ovarian resumption and cyclicity were the loss of BC [OR=3.3, CI 95% (1.2-13.3) (p<0.05)] and lameness [OR= 9.0, CI 95% (1.2-13.3) (p<0.05)]. Conclusions. Although the emergence of postpartum follicular waves was observed early, under the experimental conditions of this study there are factors that may affect the first ovulation favoring the occurrence of anovulatory conditions. The determinant factors were low body condition and lameness.